Thin Capitalization dan Koneksi Politik dalam Mendorong Agresivitas Pajak yang Dimoderasi oleh Kepemilikan Institusional - Azzahra Fayza Nabila; Aditya Hermawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This studi is motivated by data indicating that energy sector companies in Indonesia rank 11th among 30 countries with the lowest tax complience rates. Using a quantitative approach, this research investigates the factors influencing tax avoidance behavior in the energy secotr. Moderated Regression Analysis (MRA) was applied to data from 48 IDX-listed energy companies, selected based On the Job Training specific criteria and analyzed using Eviews version 12. The result reveal that political connections significanly affect tax aggresiveness. However, this effect weaknes when moderated by institutional owership, which shows a significant but negative interaction. In contrast, thin capitalization and its interaction with the moderating variable do not exhibit any significant influence.